• The ocean as a bridge and a barrier between Africa and Europe: Fatou Diome’s Le Ventre de l’Atlantique - Ravera, Elena (Oltreoceano - Rivista sulle migrazioni, 2024)
As foregrounded in the very title of Fatou Diome’s postcolonial autofiction, Le Ventre de l’Atlantique (2003), the Atlantic Ocean is an indispensable and persistent leitmotif that infiltrates both the words and the pages. The text tells the story of Salie, a young Senegalese woman based in Strasbourg, France, while Madické, her little half-brother, still lives in Senegal, on the small island of Niodor. Although she tries to discourage him, the boy would like to join his sister in Europe to pursue his dream of meeting his idol Paolo Maldini and becoming a professional football player. The telephone is their only means of contact in the immense, deep waters that separate them and, at the same time, unite their destinies. While the writer effectively deconstructs the contrast between the myth of a Europe-Eldorado and the dystopia of a poor and hopeless Africa, she also shows the reader how the ocean has many ambiguous and heterogeneous interpretations: on the one hand, the Atlantic can be a prodigious bridge, a liquid umbilical cord connecting the two continents, but, on the other, it is also a hostile and dangerous border, which becomes a tomb for some of the characters in the book. The aquatic presence accompanies the narration not only at the thematic level, but also through several aesthetic and rhetorical solutions, such as the use of metaphor, personification and zoomorphism, as well as of a fluid writing technique which mimics the wave movements of the sea. The article aims to study this stylistic and thematic polymorphism of the Atlantic in Diome’s novel, trying to show its importance for the construction of the author-narrator’s Afro-European identity.